Temperature Effects on Cultural and Morphological Aspects of Ascochyta fabae Sand, Agent of Ascochyta Blight on Faba Bean (Vicia faba L. Subsp. Major) - Benzohra, Ibrahim Elkhalil; Bendahmane, Boubekeur Seddik; Youcef Benkada, Mokhtar; Labdi, Mohamed (Advances in Biological Research, 2018)
Ascochyta fabae is a major parasite of faba bean causes ascochyta blight disease. Two controlled condition experiments were conducted to study the temperature effect on mycelial growth and sporulation of A. fabae, 5 days after incubation. The maximum average of mycelial growth was 75 mm on 5 days and sporulation was 24 × 103 conidia ml 1 and mycelial growth was increasing by 15 mm day 1, were recorded at 22°C. The least values of these parameters were obtained in 26 and 30°C. Such parameters were linearly increased with temperature to maximum and declined progressively in both reaction evaluation tests. The two evaluation tests indicated
Keywords: Faba Bean; Ascochyta fabae; Ascochyta Blight; Mycelial Growth; Sporulation